THE FORMATION OF A NEW INFORMAL POLITICAL PRACTICES OF ISLAMIC RADICALS - G. V. Volgushev (Современная наука и инновации, 2022)
"Islamic state" (IG or ISIL), the decline of which was approached by the forces of the Russian army in 2017, within three years of its existence demonstrated the formation of informal political practices of radical Islamists, which were not previously practiced by Islamists and were not predicted by the scientific community. As a result, the informal political practices of radical Islamism have undergone not only quantitative but qualitative changes. The very same essence of the phenomenon under consideration has not changed, it has remained at the level of terror, unacceptable practices prohibited by the laws of countries and peoples to combat "infidels" and secular governments.